Can a posterior approach effectively heal thoracic and lumbar tuberculosis? Microbiology outcomes of the operative area - Chen Zhao; Xiaobing Pu; Qiang Zhou; Xingzhou Huang; Chengmin Zhang; Lei Luo; Zehua Zhang; Tianyong Hou; Fei Luo; Fei Dai; Jianzhong Xu (Journal of Orthopaedic Surgery and Research, 2019)
Abstract Background There was a controversy about surgery approach of thoracic and lumbar tuberculosis (TB) treatment. The aim of this study was to compare the microbiology outcomes of the drainage liquid and the clinical outcomes of a posterior and anterior approach in the treatment of thoracic and lumbar TB. Materials and methods A total of 105 patients were enrolled in this prospective study from February 2011 to September 2015. Patients were divided into two groups: group A (51 patients, posterior approach surgery) and group B (54 patients, anterior approach surgery). Intraoperative TB samples were sent for Mycobacterium tuberculosis culture (MTBC). Drainage fluid was postoperatively collected for polymerase chain reaction (PCR), acid-fast strains (AFS), MTBC, and DNA molecular detection (DNAMD) analyses. Compare the drainage liquid positive rate of the two groups and estimate relationship between the positive results of drainage fluid and the lesion region. In addition, the clinical outcomes including the bony fusion, relapse rate, complications, and neurological status were collected. Results There was no significant difference in the positive rate of AFS, PCR, DNAMD, MTBC, or any positive rate (APR) of drainage liquid between the two groups (P > 0.05). In both groups, the MTBC-positive rate of postoperative drainage fluid was significantly lower than that of the intraoperative sample (P < 0.01). There was no significant relationship between APR and the lesion region (P > 0.05). All the patients had at least 2 years of follow-up, with an average of 34.4 ± 15.8 months. There were four patients in group A and two patients in group B who had recurrent spine TB, and the rest of the patients had fusion in the surgical area. There was no significant difference in the incidence of TB recurrence or other complications between the two groups (P > 0.05). All the patients with neurological dysfunction had improved after surgery. Conclusion Compared with anterior approach surgery, posterior approach surgery had equal effectiveness of debridement. The two kinds of surgery can effectively clear the lesions surrounding the spine and heal thoracic and lumbar TB.